The Relationship between Exposure to Arsenic in Drinking Water and the Prevalence of Diabetes Mellitus in Two Urban Populations in the Southeastern Areas of Iran - Mohammad Kahnooji; Maryam Karimifar; Mahdieh Azin; Hassan Ahmadinia; Seyed Ahmad Razavi; Ali Mohammad Madahian; Hadi Eslami (Journal of Environmental Health and Sustainable Development, 2023)
Introduction: Chronic exposure to Arsenic (As) can increase the risk of diabetes mellitus. This study aims to determine the relationship between exposure to the As by drinking water and the prevalence of diabetes mellitus in two urban populations of Rafsanjan and Kashkuyeh, Iran, in 2020. Materials and Methods: In this research, 120 participants from Rafsanjan and Kashkuyeh were recruited and divided into four groups. The first two groups have lived in Rafsanjan and Kashkuyeh for the past 10 years, and the second two groups have lived in these two cities for less than a year. Individuals with two episodes of fasting blood glucose (FBG) ≥ 126 mg/dl were considered to have diabetes. Results: As was found in high levels in all samples (10 samples) in Rafsanjan and 55% of samples (10 samples) in Kashkuyeh. The prevalence of diabetes was significantly higher in people with a residence duration of more than 10 years (p = 0.038). The analysis of Multiple Logistic Regression model demonstrated that the chance of developing diabetes in people who had lived in either city for more than 10 years was almost 5.7 times higher than others (OR = 5.79; P = 0.003). Also, the chance of developing diabetes was 91% higher in people who had lived in Rafsanjan compared with Kashkuyeh, and 91% higher in men than in women (OR = 1.915; P = 0.215). Conclusion: Chronic exposure (≥ 10 years) to high levels of As by drinking water can increase the risk of diabetes, and future research is needed in this regard.